Performance and Dialogue Skills of TV news Broadcasters - Hassan Al-Saadi, Islam; Ali Nour, Hussein (ALBAHITH ALALAMI, 2021)
Television is one of the best means of transmitting news, as it presents to us the events and facts in our homes in an integrated manner that depends in their formation on the two elements of sound and image, as they relate to the different emotions of each individual as long as he enjoys the blessings of hearing and sight, in addition to that the image is of great importance and is the basis of persuasion for the recipient, which is stronger An influence from the audio or readable word, at a time when the reader of the newsletter (the broadcaster) should have high performance and preventive skills and a distinguished profession in his work, and the only authority that has the right to judge this is the viewer himself. The performance and preventive skills and their role in enhancing the semantics of meaning in the television news bulletin are among the most important pillars that are examined in evaluating the work of the broadcaster on the news bulletin. It is technical, aesthetic and intellectual, as it allows the recipient to reformulate his ideas in the light of the reception in line with his awareness and knowledge references. Conducting a survey study for broadcasters on Iraqi satellite channels facilitates the researcher’s work to find professional and objective answers, as he has skill, performance and performance, as well as professional competence, great courage and self-confidence, through news bulletins and in all satellite stations, which are a template for a group of local, Arab and international news.